The Intoxication of Power Interdisciplinary Insights - Garrard, Peter; Robinson, Graham; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
The Intoxication of Power is a collection of contributions by thirteen authors from various academic disciplines sharing a concern for the development of understanding of the nature and origins of leadership hubris. The book originated at conferences held by the Daedalus Trust, which fosters research into challenges to organizational well-being.
Keywords: Business; Management; Leadership; Organization; Planning; Behavioral economics; Development economics; Business and Management; Business Strategy/Leadership.; Organization; Management; Development Economics; Behavioral/Experimental Economics; Electronic books